Piagam Madinah Strategi Sosial Ala Rasulullah Dalam Membangun Masyarakat Rahmatan Lil’alamin - Ana Aulia Hanifah (CV. ITTC INDONESIA, 2025)
The Charter of Medina represents tangible evidence of the Prophet's wisdom in developing social strategies within a heterogeneous society. This research aims to reveal the importance of regulation within a society or group to build an orderly and harmonious community. This study employs qualitative research with a descriptive-analytical approach, utilizing library research methodology, thereby using books, journals, and other literature to support data collection. The results of this research are, first, the Prophet Muhammad SAW was able to regulate a harmonious society by adhering to Islamic values manifested in the Charter of Medina. Second, there is relevance between the Charter of Medina and Indonesian society as a multicultural nation.